The boy from the sea - Carr, Garrett, 1975- (Alfred A. Knopf, 2025)
"1973. In a close-knit community on Ireland's west coast, a baby is found abandoned on the beach. Named Brendan Bonnar by Ambrose, the fisherman who adopts him, Brendan will become a source of fascination and hope for a town caught in the storm of a rapidly changing world. Ambrose, a man more comfortable at sea than on land, brings Brendan into his home out of love. But it's a decision that will fracture his family and force him to try to understand himself and those he cares for. Bookended by the arrival and departure of a single mesmerising boy, Garrett Carr's The Boy From the Sea is an exploration of the ties that make us and bind us, as a family and community move irresistibly towards the future"--